A new species of Lamelligomphus Fraser, 1922 (Odonata: Gomphidae) from southern Yunnan, China - Zhang, Hao-Miao; Yang, Guo-Hui; Cai, Qing-Hua (Zootaxa, 2016)
Lamelligomphus annakarlorum sp. nov. is described based on specimens collected from southern Yunnan Province, China (holotype male: Xishuangbanna National Nature Reserve, 21°57’59’’N, 101°12’37’’E, Xishuangbanna Dai Autonomous Prefecture, Yunnan Province, China). All type specimens of the new species have been deposited in the Collection of Aquatic Animals, Institute of Hydrobiology, Chinese Academy of Sciences, Wuhan City, Hubei Province, China. It is compared with Lamelligomphus camelus (Martin, 1904), which shares some similar characters.